The Influence of Affective Variables On EFL/ESL Learning and Teaching - Riryn Fatmawaty (Universitas Islam Lamongan, 2017)
One of two domains of learning is the affective domain. It is defined as the emotional side of human behavior. When instructional designers consider the affective domain, they frequently think only in terms of a students motivation to learn. And motivation is certainly important, as a students attitude toward a given course or subject area can be a contributing factor to his achievement in it. The interest in affective variables in language learning is reflected in some modern teaching stances aimed at reducing anxiety and inhibitions and enhancing the learners motivation and self-esteem. These approaches could be identified within the so-called humanistic education. Humanistic education takes into consideration that learning is affected by how students feel about themselves. It is concerned with educating the whole person the intellectual and the emotional dimensions. EFL/ESL learning and teaching should be aimed at establishing meaningful communication in the classroom, and the first requirement towards this end is an affective affirmation of the student. Perhaps there is a need for further research to determine the effects of different approaches and methods; yet what is needed, is awareness that a focus on the subject matter of learning, is no longer enough to develop the ultimate aim of education: love of learningKeywords: Affective, EFL/ESL